Cloning and Expression of β-(1,3-1,4) Glucanase (Lichenase) Gene in Bacillus subtilis RSKK246 to create new Probiotic in aquaculture - ÇAM,ÖZGEN A. (2022)
Abstract β-Glucan is an essential component of the cell walls of grains such as oats and barley. 1,3-1,4-β-D-glucan 4-glucanhydrolase (β-glucanase or lichenase) (EC 3.2.1.73) is an enzyme with the ability to hydrolyze β-glucans. In this research, β-Glucan which is a good source of feed additive fish probiotics, was used in order to benefit from feed quality in fishery products, to increase live weight gain and to strengthen the immune system. In this study, recombinant vector pNW33N carrying the β-(1,3-1,4) glucanase (lichenase) gene of Streptococcus bovis genome was transferred to Bacillus subtilis RSKK246 (CMCase+) strain by electroporation. Subsequently, electrotransformation was performed on LB-agar plates containing lichenan and enzymatic activity regions of recombinant B. subtilis RSKK246 colonies were observed by staining with Congo red. In addition, the DNA from the recombinant plasmid pNW33N+Lichenase (pNW33NLic) was cut on both the BamHI and HindIII endonucleases and observed on the lichenase gene (1800 bp) agarose gel. On the other hand, the protein band corresponding to 26 kDa of the recombinant enzyme was observed by zymogram analysis. These results indicate that the β-(1,3-1,4) glucanase gene has been successfully expressed to the B. subtilis strain RSKK246.